The Boy Travellers in the Far East, Part Second : Adventures of Two Youths in a Journey to Siam and Java; With Descriptions of Cochin-China, Cambodia, Sumatra and the Malay Archipelago - Knox, Thomas Wallace, 1835-1896 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Boy Travellers in the Far East, Part Second" by Thomas Wallace Knox is a travel narrative and adventure story written in the late 19th century. The book continues the journey of two youths, Frank and Fred, who travel with Doctor Bronson as they explore the exotic regions of Siam, Java, and surrounding countries, documenting their experiences and observations. It combines elements of adventure and education as the characters encounter various cultures, landscapes, and historical insights along their travels. At the start of the book, Frank, Fred, and Doctor Bronson are in Hong Kong, eagerly awaiting news from home via the arrival of the Pacific Mail steamer, "City of Peking." Upon receiving encouraging letters that confirm their planned journey around the world, they enthusiastically discuss their next steps. Doctor Bronson proposes a route that takes them to Saigon, Cochin China, and eventually to Siam, indicating that while they may face some challenges, the rich experiences and sights awaiting them will make the journey worthwhile. The boys demonstrate a keen interest in learning about their surroundings, hinting at the educational underpinnings of their adventure as they set sail for new discoveries. (This is an automatically generated summary.)
Release date is 2018-10-26
Produced by Annie R. McGuire
Keywords: Thailand -- Description and travel -- Juvenile literature; Java (Indonesia) -- Description and travel -- Juvenile literature; East Indies -- Description and travel -- Juvenile literature